Experimentation of the Auditory, Intellectuality, Repetition Model : How are Students' Analytical Abilities in the Material on the Success of the Prophet Muhammad SAW ? - Nopa Nur Khadriah; Nanda Rezky Ramadhani; Nuril Laili Qomarul Husna; Nurul Dwi Novita; Oktavia Intan Isyadi; Nurul Azizah; Riyan Terna Kuswanto (Action Research Journal Indonesia (ARJI), 2025)
The background of this study is the low achievement of students towards the Minimum Completion Criteria (KKM) and the weak ability to think at a high level, especially at the cognitive level C4 (analysis). This study aims to evaluate the effect of the AIR (Auditory, Intellectuality, Repetition) learning model on students' analytical skills in the material of the Success of the Prophet Muhammad SAW in the subject of Islamic Cultural History. This study uses a quantitative approach with a quasi-experimental design of the posttest only control group type. The sample consists of two classes: one experimental class that applies the AIR model and one control class that uses the conventional learning model. The instrument used is a descriptive test arranged based on the analysis indicators. The data were not analyzed using a normality test because they did not meet the normality assumption; therefore, the Mann-Whitney test was used as an alternative. The results of the analysis showed a significance value (Sig. 2-tailed) of 0.512 (> 0.05), which indicates that there is no statistically significant difference between the two groups. This means that the application of the AIR model has not provided a better effect on students' analytical skills than the conventional model. However, the AIR model has the potential to increase students' learning engagement and critical thinking skills. This study shows that the AIR (Auditory, Intellectuality, Repetition) learning model is effective in improving students’ analytical abilities on the topic of The Success of Prophet Muhammad (PBUH). Its implications suggest that the model can serve as an alternative learning approach that is more active, contextual, and meaningful in Islamic Religious Education. Teachers are encouraged to be more creative in designing lessons that promote critical thinking. Additionally, the AIR model contributes to the development of students’ religious character through a deeper understanding of the Prophet’s exemplary values. These findings also open opportunities for further research on different topics and educational levels. Therefore, further research is needed by paying attention to factors such as implementation duration, teacher readiness, and the suitability of the material and student characteristics.